Double breasting repair of urethral fistula in a patient with perineal abscess secondary to a large urethral stone - Dwivedi Sankalp; S. R. Joharapurkar; Deshmukh Abhay (Indian Journal of Plastic Surgery)
We report here a case of urethral fistula managed successfully following incision and drainage for the urethral abscess secondary to a large urethral stone leading to a large diverticulum (another rare condition) by using the technique of double breasting, where we used the redundant urethra and overlying skin